Ethical issues in non-intervention trials for thyroid cancer. Issue 3 (March 2018) - Angelos, P.; Hartl, D.M.; Shah, J.P.; Nixon, I.J.; Owen, R.P.; Rinaldo, A.; Rodrigo, J.P.; Shaha, A.R.; Silver, C.E.; Suárez, C.; Ferlito, A.
Abstract: In recent years, the increasing numbers of small, apparently indolent thyroid cancers diagnosed in the world have encouraged investigators to consider non-intervention as an alternative to surgical management. In the following pages, the prospect of a non-intervention trial for thyroid cancer is considered with attention to the ethical issues that such a trial might raise. Such a non-intervention trial is analyzed relative to 7 ethical considerations: the social or scientific value of the research, the scientific validity of the trial, the necessity of fair selection of participants, a favorable risk-benefit ratio for trial participants, independent review of the trial, informed consent, and allowing the study participants to withdraw from the trial. A non-intervention trial for thyroid cancer is also considered relative to the central concept of equipoise.